1995
DOI: 10.1002/prot.340220210
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of hydrophobicity, amphiphilicity, and α‐helicity on the activities of antimicrobial peptides

Abstract: Multiple linear regression was used to quantify the dependence of the antimicrobial activity of 13 peptides upon three calculated or experimentally determined parameters: mean hydrophobicity, mean hydrophobic moment, and alpha-helix content. Mean hydrophobic moment is a measure of the amphiphilicity of peptides in an alpha-helical conformation. Antimicrobial activity was quantified as the reciprocal of the measured minimal inhibitory concentration (MIC) against Escherichia coli. One of the peptides was magaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
65
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 15 publications
4
65
0
Order By: Relevance
“…From observation of the major conformation, it is evident that under these conditions, GS14K4 partially exists in a ␤-sheet-like secondary structure as evidenced by the and torsion angles that fall within the range for a antiparallel sheet. There is also evidence from the ensemble for proximity of cross-strand atoms, including the ␣-protons of residues 4 and 9 and residues 2 and 11, and for the expected cross-strand hydrogen bonds between Leu 3 and Val 10 , Lys 5 and Leu 8 , and Val 1 and Leu 12 , thus further indicating that this diastereomer exists in a ␤-sheet-like conformation. In addition, the two type IIЈ ␤-turns that are present in GS14 are also observed in a similar conformation in GS14K4 and therefore allow the two strands to be brought into proximity to form the antiparallel sheet.…”
Section: Nmr Spectroscopy and Structure Determination Of Gs14k4mentioning
confidence: 92%
“…From observation of the major conformation, it is evident that under these conditions, GS14K4 partially exists in a ␤-sheet-like secondary structure as evidenced by the and torsion angles that fall within the range for a antiparallel sheet. There is also evidence from the ensemble for proximity of cross-strand atoms, including the ␣-protons of residues 4 and 9 and residues 2 and 11, and for the expected cross-strand hydrogen bonds between Leu 3 and Val 10 , Lys 5 and Leu 8 , and Val 1 and Leu 12 , thus further indicating that this diastereomer exists in a ␤-sheet-like conformation. In addition, the two type IIЈ ␤-turns that are present in GS14 are also observed in a similar conformation in GS14K4 and therefore allow the two strands to be brought into proximity to form the antiparallel sheet.…”
Section: Nmr Spectroscopy and Structure Determination Of Gs14k4mentioning
confidence: 92%
“…Several studies have shown that on the angle of helix content the mean hydrophobic moment is a more important factor affecting antimicrobial activity than hydrophobicity (Pathak et al, 1995;Fernandez-Vidal et al, 2007). The measurements of the interfacial partitioning of a family of 17-residue amidated-acetylated peptides into both neutral and anionic lipid vesicles showed that peptide helicity in water and interface increased linearly with hydrophobic moment, as did the favorable peptide partitioning free energy.…”
Section: Amphipathicity and Hydrophobic Momentmentioning
confidence: 99%
“…An increase in the antimicrobial activity of a linear ␣-helical antimicrobial peptide has been shown in several cases to correlate closely with an increase in ␣-helical secondary structure (19,20). To examine the contribution of ␣-helical secondary structure to the antimicrobial activity of buforin II, CD spectra of buforin II and its analogs were obtained.…”
Section: Relationship Between the ␣-Helical Content Of Truncated Bufomentioning
confidence: 99%